(untitled) (Brazilian Journal of Police Sciences, 2026)
The Soft Biometrics has had great of notoriety in recent years with the advance the biometric identification processes. As a result, the set: scars, marks and tattoos (SMT’s ) has been increasingly used in Verifications Process purposes in the field of criminal sciences to identify criminals who commit sex crimes with the producing pornographic material. This is due to the fact that in child sexual abuse images, for example, the criminal hardly appears, leaving exposed reduced parts of his body, such as the dorsum of the hands. In this sense, the objective of this paper is to propose an approach to ACE-V methodology for forensic comparison of images of the dorsum of the hands to indicate if they are related to the same person. This paper proposes the stages of Analysis, Comparison, Evaluation and Verification for cases in which there is a Verification Process of Soft Biometrics of the dorsum of the hands. The improvement of the steps in the field of practice and possible approaches for the necessary progress of this still incipient field are also highlighted.